Functional imaging of lung cancer using dual energy CT: how does iodine related attenuation correlate with standardized uptake value of 18FDG-PET-CT? - Schmid-Bindert, Gerald; Henzler, Thomas; Meyer, Mathias; Dinter, Dietmar; Apfaltrer, Paul; Kriššák, Radko; Manegold, Christian; Schönberg, Stefan; Fink, Christian (European radiology, 2011)
Objectives:To investigate the correlation between maximum standardized uptake value (SUVmax) of 18FDG PET-CT and iodine-related attenuation (IRA) of dual energy CT (DECT) of primary tumours and 18FDG PET-CT positive thoracic lymph nodes (LN) in patients with lung cancer.Methods37 patients with lung cancer (27 NSCLC, 10 SCLC, 86 18FDG PET-CT positive thoracic LN) who underwent both 18FDG PET-CT and DECT were analyzed. The mean study interval between 18FDG PET-CT and DECT was ≤21 days in 17 patients. The mean and maximum IRA of DECT as well as of virtual unenhanced and virtual 120 kV images of DECT was analyzed and correlated to the SUVmax of 18FDG PET-CT in all tumours and 18FDG PET-CT positive thoracic lymph nodes. Further subgroup analysis was performed for histological subtypes in all groups.ResultsA moderate correlation was found between SUVmax and maximum IRA in all tumours (n = 37;r = 0.507;p = 0.025) whereas only weak or no correlation were found between SUVmax and all other DECT measurements. A strong correlation was found in patients with study intervals ≤21 days (n = 17; r = 0.768;p = 0.017). Analysis of histological subtypes of lung cancer showed a strong correlation between SUVmax and maximum IRA in the analysis of all patients with NSCLC (r = 0.785;p = 0.001) and in patients with NSCLC and study intervals ≤21 days (r = 0.876;p = 0.024).Thoracic LN showed moderate correlation between SUVmax and maximum IRA in patients with study intervals ≤21 days (r = 0.654; p = 0.010) whereas a weak correlation was found between SUVmax and maximum IRA in patients with study intervals >21 days (r = 0.299; p = 0.035).ConclusionsDECT could serve as a valuable functional imaging test for patients with NSCLC as the IRA of DECT correlates with SUVmax of 18FDG PET-CT.
Gesehen am 18.05.2018